2018
DOI: 10.1053/j.gastro.2018.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obesity and Weight Change and Risk of Diverticulitis in Women

Abstract: During a 6-year follow-up period, we observed an association between obesity and risk of diverticulitis among women. Weight gain during adulthood was also associated with increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 37 publications
6
35
2
3
Order By: Relevance
“…The aim of our present study was to assess the role of genetic variations consistently identified in the three large recent GWAS 10,12,13 for the specific risks for diverticulosis and diverticulitis, respectively. Our results are in line with previous data concerning the association of diverticulosis with age and BMI as risk factors (diverticulosis) [22][23][24] , as well as alcohol consumption 25,26 and smoking status [27][28][29] as risk factors for diverticulitis.…”
Section: Discussionsupporting
confidence: 93%
“…The aim of our present study was to assess the role of genetic variations consistently identified in the three large recent GWAS 10,12,13 for the specific risks for diverticulosis and diverticulitis, respectively. Our results are in line with previous data concerning the association of diverticulosis with age and BMI as risk factors (diverticulosis) [22][23][24] , as well as alcohol consumption 25,26 and smoking status [27][28][29] as risk factors for diverticulitis.…”
Section: Discussionsupporting
confidence: 93%
“…37,38 Obesity, and central obesity in particular, increases the risk of diverticulitis. [39][40][41][42] Smoking is also associated with an increased risk of diverticulitis-particularly complicated diverticulitis. [43][44][45][46] On the other hand, dietary fiber intake and prudent diets (high in fruits, vegetables, and whole grains) reduce the risk of diverticulitis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The sixth and the seventh statement point out that diverticulosis is a merely expression of an anatomical alteration [21][22][23], while symptomatic uncomplicated diverticular disease (SUDD) may have overt inflammation microscopic inflammation even without any endoscopic inflammation [24,25]. The last two statements point out the role of high fiber diet in reducing the risk of acute diverticulitis [26][27][28][29][30], and more recent evidences are available about the role of obesity on occurrence of DD complications [31,32]. Overall consensus about these statement was very high, since all of them reached >80% agreement among respondents.…”
Section: Commentsmentioning
confidence: 99%